Philosophy and painting - Gaiger, Jason (London [England] : Bloomsbury, 2022)
"What can philosophy reveal about painting that might otherwise remain hidden or obscure? Investigating the complex relationship between what a painting represents and the means by which it is represented, Philosophy and Painting introduces and opens up current debates and ideas. Now thoroughly updated, this 2nd edition includes an additional chapter on contemporary painting, examining the work of artists such as Lynette Yiadom-Boakye, Amy Sillman, and Katharina Grosse, and coverage of topics including the post-medium condition and the digital divide. Remaining highly readable throughout, the book provides a philosophically rigorous defence of the relevance of painting in the 21st-century . It is the ideal starting point for anyone interested in the major ideas informing painting as an art. It covers: - How and why painting may be distinguished from other art forms. - The relationship between the painted surface and the depicted subject. - The "rules of representation" specific to painting. - The limits of formalism. - The most recent technological and artistic developments and their implications"--
Preface -- 1. Philosophical Questions -- 2. A Window onto the World -- 3. Surface and Subject -- 4. Resemblance and Denotation -- 5. The Specifically Visual -- 6. Modernism and the Avant-Garde -- 7. Contemporary Painting -- Bibliography -- Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Painting -- Philosophy; Art and philosophy; Philosophy: aesthetics,Painting & paintings; Electronic books